Effects of Rice Green Folder on Growth Performance in Khmer native x Hariana Crossbred Cattle - Morm, Sophany; Phoeng, Pesith; Khy, Chhady; Khoem, Senghak; Nhuong, Koemseang; Peuo, Vibol; Net, Savdy; Vong, Sokchea; Yi, Thearak; Din, Mach (AGRITROPICA : Journal of Agricultural Sciences, 2024)
This study aimed to assess the effect of rice green folder on growth performance in Khmer native x Hariana crossbred cattle. Twelve males of Khmer native x Harian crossbred cattle were assigned an initial body weight of 190±10 kg (IBW) with 62 days of feeding regimen and an average of 15 months of age. The dietary treatments were assigned in a completely randomized design (CRD), with three treatments of four replications, each containing four cows. Feeding treatments were as follows: 1) 100% commercial feed (Control), 2) 50% commercial feed + 50% natural grasses (NG-50), and 3) 50% commercial feed + 50% rice green folder (RGF-50). Cows were fed at 1.5% Body weight of dry matter (DM). The results indeed showed that the initial body weight (IBW) and final body weight (FBW) were non-significantly different (P>0.05). The Control group consumed the total feed intake between the groups NG-50 at 6.58 kg and 6.85 kg, which were similar amounts but higher than RGF-50, which was 5.79 kg daily a head (linear increased <0.05). Nevertheless, average daily gain (ADG) in Control, NG-50, and RGF-50 was linearly increased (P<0.05) as the ADG was 0.58, 0.46, and 0.39kg/head. FCR in the NG-50 and RGF-50 were in the same row and higher than Control, with the precious value in both NG-50 and RGF-50 at 14.90 higher than 11.45 Control (P<0.001).  In conclusion, RGF-50 was a suitable roughage supply for feedlot cattle and could improve economic effectiveness. Thus, RGF was recommended for further study.